2020
DOI: 10.20944/preprints202007.0207.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Catchment-Scale Flood Modelling in Data-Sparse Regions Using Open-Access Geospatial Technology

Abstract: Consistent data is seldom available for whole-catchment flood modelling in many developing regions, thus this study demonstrates how the complementary strengths of open and readily available geospatial datasets and tools can be leverage to map flood risk within acceptable levels of uncertainty for flood risk management. Available fragmented remotely-sensed and in situ datasets (including hydrological data, altimetry, digital elevation model, bathymetry, aerial photos, optical and radar imageries) are s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…The study by Fang et al [4] found many differences among time of concentration that were estimated using different formulas using parameters of watersheds. The importance of a suitable model for estimating the concentration-time useful for accurately predicting flow rates from hypothetical storms becomes necessary in the study area [5,6]. This is because Anambra State has recently been hit by floods and the government is looking for ways to effectively manage and avoid subsequent devastation.…”
Section: Introductionmentioning
confidence: 99%
“…The study by Fang et al [4] found many differences among time of concentration that were estimated using different formulas using parameters of watersheds. The importance of a suitable model for estimating the concentration-time useful for accurately predicting flow rates from hypothetical storms becomes necessary in the study area [5,6]. This is because Anambra State has recently been hit by floods and the government is looking for ways to effectively manage and avoid subsequent devastation.…”
Section: Introductionmentioning
confidence: 99%